Japanese chum salmon reproductive traits - Hasegawa, Koh; Okamoto, Yasutaka; Morita, Kentaro (Dryad, 2021)
Geographic clines in life-history traits are often recognized as
adaptations to the associated transitional environments. As life-history
traits evolve in response to anthropogenic processes, these geographic
clines can change over time. The geographic and temporal trends of
reproductive traits in Japanese chum salmon Oncorhynchus keta were
analyzed. Data were collected from 23 rivers located between 36° and 45°
north latitude and 136° and 146° east longitude from 1994 to 2010. We
confirmed the geographic clines of reproductive traits: relative gonad
weight increased in more northeasterly locations, and females had fewer,
but larger, eggs in more northeasterly locations after standardization by
body size. The geographic clines changed over the years. The northeastward
geographic trend of increasing gonad weight became more pronounced over
time. Temporal trends toward smaller but more numerous eggs were evident,
especially in northeasterly locations. Under natural and sexual selection,
gonadal investment should be constrained by the energetic demands of the
cost of migration, particularly in southwesterly locations (which are
farthest from the feeding grounds), and by breeding competition during
natural reproduction. In addition, females should have fewer but larger
eggs owing to constraint on growth opportunities for their offspring in
more northeasterly regions of Japan, which are colder and have less
available food. However, global warming may mitigate this constraint on
growth opportunities in northeastern Japan by increasing river water
temperatures. Moreover, we consider that relaxation of the effects of
natural and sexual selection on intense breeding competition and of early
growth conditions has occurred through domestication selection by hatchery
programs. These may have caused temporal shifts in geographic clines. We
should consider several co-occurring anthropogenic impacts on natural and
sexual selection when evaluating the life-history traits of organisms. For
the sustainable use of biological resources, maintaining geographically
adapted life-history traits during adaptation to climate change is
essential. Therefore, the conservation of wild salmon populations formed
by natural selection is preferable to the stocking of hatchery-reared fry.